DAMPAK IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (Studi Kasus Pada Pasien Rawat Inap di Rumah Sakit Islam Surakarta) - Supriyono, Supriyono (-)
The study was conducted to impact implementation of relationship marketing to customer satisfaction and loyalty. This study used models of relationship marketing that includes four independent variables, namely: understanding customer expectations, cooperation with the customer, employee empowerment and service quality.In connection with the above research objectives, to identify problems, research is taking place in Surakarta Islamic Hospital. population in this study were inpatients in Surakarta Islamic Hospital. A total of 100 respondents sampled with sampling techniques using non-probability sampling quota sampling manifold. Method of data collection using the results of the primary data distribution of questionnaires filled out by the respondents.The test results of path analysis it can be concluded that the direct effect understand customer expectations, collaboration with customers, service quality on customer loyalty > of the indirect influence that customer satisfaction can not be intervened 3 variables influence the effect on customer loyalty in Surakarta Islamic Hospital and only customer satisfaction could intervened influence employee empowerment on customer loyalty in Surakarta Islamic Hospital.         From the results of these studies suggest that researchers need to maintain and continue to implement employee empowerment in improving the quality of care with more intensive to provide training and developments to employees, improve collaboration with customers and trying to    better understand customer expectations.Keywords   :    Relationship  marketing, Customer satisfaction, Customer loyalty, Quality of service